Leverage and preemptive selling of financial institutions - Bernardo, Antonio E.; Welch, Ivo (Journal of Financial Intermediation, 2013)
In our model, financial firms’ leverage choices and asset sales impose negative externalities on other financial firms. This means that individual firms cannot determine their optimal capitalizations in isolation, but have to take the aggregate financial sector characteristics into account. In particular, they become more aggressive when their peers are more conservative. Furthermore, financial firms over-consume liquidity in equilibrium. For some parameter regions, small parameter changes can induce large differences in the equilibrium allocation of risk. Historical experience is not necessarily a good guide as to whether the prevailing equilibrium is fragile or not.